Protein characterization and fatty acid composition of VHDL subfraction II of the spider Polybetes pythagoricus - Laino, Aldana (2015)
VHDL fraction contains hemocyanin as its major apoprotein and transports most of the circulating lipids in the spider Polybetes pythagoricus (Sparassidae). This work shows that subfraction II (the major VHDL component) is composed of a single protein of 420 kDa under native conditions and three subunits, 67, 105 and 121 kDa under denaturing conditions. Circular dichroism indicated that this subfraction contains 20% α-helix, 29% β-sheet, 22.7% turns and 29.7% unordered structures. Comparison of trypsin susceptibility showed that the 105 and 121 kDa subunits were more susceptible indicating that these proteins would be more exposed to the aqueous medium. Peptide mass fingerprinting of the 67 and 105 kDa subunits indicated the 67 kDa subunit is similar to subunit 3 of the spider Cupiennius salei hemocyanin (21% sequence similarity), whereas the 105 kDa subunit is similar to a protein from the mosquito Anopheles gambiae (20% sequence similarity). The N-terminal amino acid sequence from subunit of 121 kDa was also determined. In relation to fatty acids, 16:0, 18:0, 18:1 and 18:2 were found to be the major components. These data provide a better understanding of VHDL subfraction II structure, which is responsible for most lipid transport in the spider P. pythagoricus.